An usual approach to treatment of a case of multidrug resistance Pseudomonas aeruginosa peritonitis: parenteral and intraperitoneal aminoglycosides and parenteral colistin - Ian May; Maha Abu-Khdeir; Roland Alexander Blackwood (MDPI AG, 2012)
Infections caused by Pseudomonas aeruginosa are becoming more common and increasingly more difficult to treat due to the continued development of drug resistance. While sensitivity to colistin (polymyxin E) is well known, it is frequently avoided due to concerns of nephrotoxicity. Reported here is a case of a multi-drug resistance pseudomonal typhlitis, bacteremia and pleural cavity infection that required significant intensive care, and serial abdominal washouts. Intra-peritoneal tobramycin in combination with broad-spectrum intravenous antibiotics including colistin were used. Several instillations of tobramycin into the abdominal cavity along with concomitant IV administration of colistin, ceftazidime and tobramycin and per os colistin, tobramycin and nystatin resulted in the clearance of the pseudomonal infection without any evidence of toxicity from the treatment. Intra-abdominal tobramycin with parenteral colistin therapy can be used in complicated clinical settings with appropriate nephroprotection.